ACTIVITY OF RELIGIOUS EDUCATIONAL INSTITUTIONS IN UZBEKISTAN IN THE YEARS OF INDEPENDENCE - Murodov Shuhrat Komil o‘g‘li (Journal Park Publishing, 2023)
It consists of a special study of the educational activities of Islamic educational institutions of a new type established in 1991-2022, the participation of the state and Islamic organizations in this process, and the study of literature on the history and historiography of the problem. Based on the theoretical methods of historiography and the study of history, the following main tasks were defined in the research: to identify the main features of the concepts in the researches on the history of religious education; categorization and classification of sources and literature on the history of Islamic education; inclusion of archival data on the studied problem, which have not yet been involved in research, for scientific use; increase the content and essence of the government's policy in the field of religion in different years based on research analysis; to identify the researches created abroad on the issue, to increase the essence of their views on the issue of religion and religious education; to show the role and importance of educational institutions in the business and foreign policy of the government in the field of religion after independence; elucidating the state of official religious education in Uzbekistan by researching the educational work of Mir Arab, Baraqkhan Madrasa, International Islamic Academy and Tashkent Islamic Institute; by studying the daily life of madrasa students, showing the rules or prohibitions of the existing system, rules of etiquette; analysis of sociological and psychological aspects of the problem; to show the contribution of Uzbekistan to the development of Islamic culture in the years of independence with the example of Islamic educational institutions.
Keywords: Religion, madrasa, education, hujra, khanaqah, Sadum, atheistic, Ko`kaldosh, Barakkhan, ISESСO, freedom of conscience, seminary, religious tolerance, higher institution, mudarris, Holy Quran, foundation, mosque, Forjak, Narshahi, Imam Bukhari, Imam Termizi, hadith science, Kalabad.